PROSPECTS OF USING NATIONAL GEOSPATIAL DATA INFRASTRUCTURE TO SOLVE MILITARY APPLICATION PROBLEMS - Korenets, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
Current trends in the development and reform of the Armed Forces of Ukraine necessitate the involvement of geographic information technologies in the military sphere. Geoinformation support of troops is an important component in decision-making at all levels of military management and in solving military-applied tasks. At present, the urgent task is the creation, implementation and practical application of automated geographic information subsystems of troops, which can increase the efficiency and effectiveness of the tasks of topographic and navigational support of troops (forces) of the Armed Forces of Ukraine. The national geospatial data infrastructure (NGDI) is a system that includes organizational structure, hardware and software, basic and profile geospatial data, metadata and metadata databases, geospatial data services, norms, rules and national standards for production, updating, processing, storage, supply and use of geospatial data that are available in Ukraine. Significant changes in the organizational, legal and technological support of the NGDI, which are associated with the adoption of the Law of Ukraine "About national geospatial data infrastructure" and the creation of a geoportal, provide new opportunities for its use for various purposes, including military tasks. The paper considers two main blocks of using NGDI to solve military-applied tasks: geoinformation support for planning and combat use of units of the Armed Forces of Ukraine and the use of NGDI for logistics, legal support and other defense needs.